PENURUNAN KADAR TSS, BOD5 DAN TOTAL COLIFORM MENGGUNAKAN HORIZONTAL ROUGHING FILTER - Edhi Sarwono; Musfik Harits; Budi Nining Widarti (Mulawarman University Press, 2017)
AbstractWater is the primary needs for any activities. Aside from fulfill the daily needs as cooking, washing, bath and sanitation, the water require to fulfill the economic activities and social as, industry, hospital, hotel, commerce, office and school. The water source can come from surface water (river, lake and reservoir) and ground water. Water that came from river, lake and reservoir, need to be treated first before it can be distributed and consumed due to potential for contaminated water. Therefore, this study has been conducted the surface water treatment using roughing filter. The study has done by using three media variations. First reactor were using gravel media with each size are 2 – 4 mm, 4 – 8 mm, and 8 – 12 mm. second reactor were using brick media with each size are 2 – 4 mm, 4 – 8 mm, and 8 – 12 mm. Third reactor were using ½ inch PVC pipe media with each size are 2 – 4 mm, 4 – 8 mm, and 8 – 12 mm. The parameters tested in this study were TSS, BOD5, and total coliform. The result of laboratory tests at the time before and after treatment on Karang Mumus river, it obtained an average removal efficiency from the three media in each roughing filter unit. The highest removal efficiency for TSS parameters were contained pipe PVC ½ inch media with average removal efficiency at 93, 32 %. The highest removal efficiency for BOD5 parameters were contained gravel media with average removal efficiency at 47,86 %. The highest removal efficiency for total coliform parameters were contained pipe PVC ½ inch media with average removal efficiency at 73,47%. Keyword: Horizontal Roughing Filter, TSS, BOD5, Total Coliform, Karang Mumus River